2000
DOI: 10.1034/j.1600-0889.2000.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

ACE-2 HILLCLOUD. An overview of the ACE-2 ground-based cloud experiment

Abstract: The ACE‐2 HILLCLOUD experiment was carried out on the island of Tenerife in June–July 1997 to investigate the interaction of the boundary layer aerosol with a hill cap cloud forming over a ridge to the north‐east of the island. The cloud was used as a natural flow through reactor to investigate the dependence of the cloud microphysics and chemistry on the characteristics of the aerosols and trace gases entering cloud, and to simultaneously study the influence of the physical and chemical processes occurring wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 1 publication
3
20
0
Order By: Relevance
“…These are 90±27 cm −3 for the remote North Atlantic and up to 180 cm −3 for the eastern North Atlantic (Bennartz, 2007). In situ observations of CDNC in the North Atlantic marine atmosphere are reported by Leaitch et al (1996), Borys et al (1998) and Bower et al (2000). Measured CDNC ranges between 50 and 400 cm −3 for relatively clean conditions.…”
Section: Cdnc and R Effmentioning
confidence: 82%
“…These are 90±27 cm −3 for the remote North Atlantic and up to 180 cm −3 for the eastern North Atlantic (Bennartz, 2007). In situ observations of CDNC in the North Atlantic marine atmosphere are reported by Leaitch et al (1996), Borys et al (1998) and Bower et al (2000). Measured CDNC ranges between 50 and 400 cm −3 for relatively clean conditions.…”
Section: Cdnc and R Effmentioning
confidence: 82%
“…However, the precise location will be a complex function of numerous variables such as the temperature at the lifting condensation level, updraft velocity, the shape and composition of the aerosol size spectrum, etc (cf., Chuang et al, 2000;Leaitch et al, 1996). For example, we note that Bowers et al (2000) found no evidence of a "role off" for aerosol concentrations until the concentrations (which encompassed both clean marine and continental pollution cases) exceeded 4000 cm −3 . On the other hand, Lu et al (2008), looking at the CDNC-AMNC relationship in polluted air in the Gulf of Mexico, reported a decrease in activation efficiency in the 400-800 cm −3 AMNC range, about the same as the "role-off" point in Martin et al Similarly, Leaitch et al (1986) found a "role-off" point for continental clouds of ∼700-800 cm −3 with a slope below this point quite similar to that derived from our data.…”
Section: Resultsmentioning
confidence: 99%
“…Bower et al, 1999;Herrmann et al, 2005). The use of hill cap clouds as a natural flow-through reactor was for example realised successfully on Great Dun Fell (UK) (Bower et al, 1999;Choularton et al, 1997;, on the German mountain Kleiner Feldberg (Wobrock et al, 1994), during the cap cloud experiment of the 2nd Aerosol Characterisation Experiment (ACE-2 HILLCLOUD) at Teneriffe, Spain (Bower et al, 2000) and during FEBUKO (Field Investigations of Budgets and Conversions of Particle Phase Organics in Tropospheric Cloud Processes) at Mt. Schmücke .…”
Section: Introductionmentioning
confidence: 99%